Platelet Counts Analysis of Platelet-Poor Plasma (PPP) Produced by Several Centrifugation Techniques - Pande Putu Rangga Raditya1 , Yetti Hernaningsih2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Platelet-poor plasma (PPP) can be obtained by various centrifugation techniques. This study aims to analyze platelet count in PPP produced by three different centrifugation techniques. Samples came from a healthy adult who underwent medical check-up and had been given informed consent. A total of 2.7 mL of blood samples were collected using three citrated tubes. Samples were centrifuged by three different techniques to obtain PPP: 1,500 g for 15 minutes twice, 3,000 g for 15 minutes, and 3,260 g for 10 minutes. The platelet count of each PPP was examined using a hematology analyzer. All three centrifugation techniques produced <10,000/µL platelets in all PPP from 31 samples. The twice centrifugation of 1,500 g for 15 minutes produced a median number of platelets which was 1×103 /µL (0-3). The 3,000 g centrifugation for 15 minutes produced a median number of platelets which was 1×103 /µL (0-5). The 3,260 g centrifugation for 10 minutes produced a median number of platelets which was 2×103 /µL (0-5). A comparison of platelet count showed a significant difference (p<0.05) among the three centrifugation techniques. The three centrifugation techniques in this study were able to produce PPP. The centrifugation technique of 1,500 g for 15 minutes twice produced the lowest number of platelets.